Evaluation of breast cancer in women under 50 in a Mastology service in the Federal District, Brazil - Vilela, Ana Cláudia Leite; Veras, Lucimara Priscila Campos; Ramos, Sérgio Eduardo Paiva; Souza, Sádia Martins de Paula; Souza, Sádia Martins de Paula (Mastology, 2021)
Introduction: Breast cancer is a relevant public health issue, and its incidence has increased in patients aged less than 50 years. This population usually receives a late diagnosis, which contributes with the poor prognosis of the condition.Objective: To assess the percentage of patients diagnosed with breast cancer before the age of 50 and compare them with the group that was diagnosed after the age of 50. Results: The general mean age was 54 years; 75.68% of the patients were younger than 50 years, aged between 40 and 49 years. Among the ones who were younger than 50, 35.14% were in stage T4; 55.41% underwent neoadjuvant chemotherapy; 16.22% presented distant metastasis; and 10.81%, locoregional metastasis. On the other hand, among those aged more than 50, 22.71% were in stage T4; 30.68% underwent neoadjuvant chemotherapy; 11.36% presented distant metastasis; and 6.82%, locoregional metastasis. Conclusion: Breast cancer in women aged less than 50 years in a Mastology service in the Federal District has been a matter of concern, for presenting more advanced tumors at the time of diagnosis; screening is still debatable.